Assessment of some liver enzyme activities in healthy Iraqi racing Horses - AH., AL-Hadithy H. (The Iraqi Journal of Veterinary Medicine, 2011)
The current study was conducted for the measurement of normal range and mean value of serum alanine aminotransferase (ALT) , aspartate aminotransferase (AST) and alkaline phosphatase (ALP) in (125) clinically normal Iraqi racing horses (males and females , Arabian and Crossbred) , aged 2 – 8 years ; < 4 , 4 and > 4 age groups . The results revealed that the range and the mean value ± SEM of these enzymes were as follows ; serum ALT 2 – 28 U/L and 11.07 ± 0.62 U/L, serum AST 30 – 210 U/L and 78.00 ± 3.62 U/L and serum ALP 63 – 204 IU/L and 96.84 ± 2.52 IU/L respectively .However, significant difference (P < 0.05) in serum ALT was recorded between Arabian and Crossbred , while serum AST values showed a significant differences (P < 0.05) between males and females , as well as between less and more than four years age groups .On the other hand , there was no significant difference in serum ALP values between the studied groups . In conclusion , this study recorded and established the normal range reference values and mean ± SEM of serum liver enzymes ALT , AST and ALP in clinically healthy Iraqi racing horses .